Rapid identification of medically important Candida isolates using high resolution melting analysis - Nemcova, Eva; Cernochova, Michaela; Ruzicka, Filip; Malisova, Barbora; Freiberger, Tomas; Nemec, Petr (PloS one, 2015)
An increasing trend in non albicans infections and various susceptibility patterns to antifungal agents implies a requirement for the quick and reliable identification of a number of medically important Candida species. Real-time PCR followed by high resolution melting analysis (HRMA) was developed, tested on 25 reference Candida collection strains and validated on an additional 143 clinical isolates in this study. All reference strains and clinical isolates inconclusive when using phenotypic methods and/or HRMA were analysed using ITS2 sequencing. Considering reference and clinical strains together, 23 out of 27 Candida species could be clearly distinguished by HRMA, while the remaining 4 species were grouped in 2 pairs, when applying the mean Tm ± 3 SD values, the shape of the derivative melting curve (dMelt curve) and, in some cases, the normalized and temperature-shifted difference plot against C. krusei. HRMA as a simple, rapid and inexpensive tool was shown to be useful in identifying a wide spectrum of clinically important Candida species. It may complement the current clinical diagnostic approach based on commercially available biochemical kits.
Keywords: DNA fungální; tranzitní teplota; Transition Temperature; fenotyp; DNA, Fungal; Phenotype; lidé; Candida; kvantitativní polymerázová řetězová reakce; Candidiasis; Humans; Real-Time Polymerase Chain Reaction; kandidóza